Left and right ventricular strain in the course of acute myocarditis: a cardiovascular magnetic resonance study - Luetkens, Julian A.; Petry, Pauline; Kuetting, Daniel; Dabir, Darius; Schmeel, Frederic C.; Homsi, Rami; Schild, Hans H.; Thomas, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To investigate the degree of impairment in left (LV) and right ventricular (RV) myocardial strain parameters over the course of acute myocarditis and to evaluate its value for the prediction of functional recovery upon follow-up.Materials and Methods 69 patients with acute myocarditis underwent cardiac magnetic resonance imaging during the acute stage (baseline) and after a mean 92.5 ± 50.4 days follow-up. Standard “Lake Louise” criteria (T2 signal intensity ratio, early gadolinium enhancement ratio and late gadolinium enhancement) and feature tracking derived LV and RV strain parameters were assessed. Logistic regression analysis was used to find predictors of functional recovery upon follow-up.Results All inflammatory parameters showed a considerable decrease over the course of the disease (P < 0.001 for all parameters). LV and RV function significantly improved on follow-up CMR (LV ejection fraction: 53.5 ± 12.7 % vs. 61.3 ± 9.5 %; P < 0.001, RV ejection fraction: 54.1 ± 10.0 % vs. 59.4 ± 6.3 %; P < 0.001). LV and RV myocardial strain (longitudinal, circumferential and radial strain) significantly improved from baseline to follow-up (P < 0.05 for all parameters). On multivariate analysis, LV global peak systolic longitudinal strain (OR: 0.303; P = 0.007) was the only independent predictor of functional recovery upon follow-up. Conclusion Alterations in LV and RV functional strain parameters occur frequently during the acute stage of myocarditis. During the course of the disease, a significant improvement in LV and RV strain parameters can be observed. It further appears that initial LV longitudinal strain may serve as a new parameter for the prediction of functional recovery upon follow-up.Key Points Citation Format
Keywords: follow-up; myocarditis; cardiac magnetic resonance; myocardial strain analysis